2021
DOI: 10.31234/osf.io/ej9a5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Raising White Resisters: Studying the Development of Anti-Racist White Children and Youth

Abstract: This article presents a developmental model of anti-racism among White children and youth. The model is informed by a structural-psychological framework which situates the development of anti-racism as inseparable from the structures and systems that uphold racial inequality. In articulating the processes by which children and early adolescents move toward becoming anti-racists, the model emphasizes foundational abilities (e.g., socio-cognitive and moral development), a developing sense of self and society (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…We identified only one study on family ethnic–racial socialization and children’s awareness of racism and white privilege before 2020 (Hagerman, 2014). Very recently, Hazelbaker et al (2021) suggested family ethnic–racial socialization as a promotive factor for the development of anti-racism orientation among white children and youth, but further empirical research on this association is needed.…”
Section: Limitations To What We Know and Directions For Future Studiesmentioning
confidence: 99%
“…We identified only one study on family ethnic–racial socialization and children’s awareness of racism and white privilege before 2020 (Hagerman, 2014). Very recently, Hazelbaker et al (2021) suggested family ethnic–racial socialization as a promotive factor for the development of anti-racism orientation among white children and youth, but further empirical research on this association is needed.…”
Section: Limitations To What We Know and Directions For Future Studiesmentioning
confidence: 99%
“…Thus, it is also important to find additional ways to include nonimmigrant origin and White youth more directly into the program. White youth play an important role in working with their peers of color to dismantle racial oppression (Hazelbaker et al, 2021) and it's intersecting partner, xenophobia (Tummala‐Narra & Sathasivam‐Ruekert, 2015), and thus White youth can benefit from greater inclusion into future programming. Findings from this study suggested that many White youth had a difficult time discovering and articulating their migration narrative.…”
Section: Practical Implicationsmentioning
confidence: 99%